2019
DOI: 10.1534/g3.118.200978
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Pseudomonas sp. Strain SCT, an Iodate-Reducing Bacterium Isolated from Marine Sediment, Reveals a Possible Use for Bioremediation

Abstract: Strain SCT is an iodate-reducing bacterium isolated from marine sediment in Kanagawa Prefecture, Japan. In this study, we determined the draft genome sequence of strain SCT and compared it to complete genome sequences of other closely related bacteria, including Pseudomonas stutzeri . A phylogeny inferred from concatenation of core genes revealed that strain SCT was closely related to marine isolates of P. stutzeri . Genes present in the SCT genome but absent from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
0
5
0
1
Order By: Relevance
“…Although rarely causing infections, over the past two decades, P. stutzeri complex members have been increasingly recognized as a cause of infection in humans ( Scotta et al, 2012 ; Hequette-Ruz et al, 2018 ; Halabi et al, 2019 ). The P. stutzeri complex has received particular attention because of specific physiological properties, such as denitrification ( Pena et al, 2012 ), nitrogen fixation ( Lalucat et al, 2006 ; Yan et al, 2008 ; Busquets et al, 2013 ; Paerl et al, 2018 ), degradation of aromatic compounds ( Brunet-Galmes et al, 2012 ; Busquets et al, 2013 ; Gomila et al, 2015a ; Hirose et al, 2015 ; Brown et al, 2017 ), and metal resistance and potential application in bioremediation ( Li et al, 2012 ; Chakraborty et al, 2017 ; Zheng et al, 2018 ; Harada et al, 2019 ). It was shown that one third of P. stutzeri complex members are naturally transformable ( Sikorski et al, 2002b ; Busquets et al, 2012 ; Smith et al, 2014 ), which may be one of the major driving forces causing its high level of intraspecific heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Although rarely causing infections, over the past two decades, P. stutzeri complex members have been increasingly recognized as a cause of infection in humans ( Scotta et al, 2012 ; Hequette-Ruz et al, 2018 ; Halabi et al, 2019 ). The P. stutzeri complex has received particular attention because of specific physiological properties, such as denitrification ( Pena et al, 2012 ), nitrogen fixation ( Lalucat et al, 2006 ; Yan et al, 2008 ; Busquets et al, 2013 ; Paerl et al, 2018 ), degradation of aromatic compounds ( Brunet-Galmes et al, 2012 ; Busquets et al, 2013 ; Gomila et al, 2015a ; Hirose et al, 2015 ; Brown et al, 2017 ), and metal resistance and potential application in bioremediation ( Li et al, 2012 ; Chakraborty et al, 2017 ; Zheng et al, 2018 ; Harada et al, 2019 ). It was shown that one third of P. stutzeri complex members are naturally transformable ( Sikorski et al, 2002b ; Busquets et al, 2012 ; Smith et al, 2014 ), which may be one of the major driving forces causing its high level of intraspecific heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…strain SCT from marine sediment (Amachi et al, 2007). Phylogenetic analyses based on 16S rRNA gene and concatenation of its core genes revealed that strain SCT was closely related to Pseudomonas stutzeri (Harada et al, 2019). Strain SCT was originally isolated as a bacterium that was able to reduce 200 μM iodate when grown anaerobically with 10 mM nitrate as the electron acceptor (denitrifying condition).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the operon mer can be either codified in the chromosome ( 69 ) or in plasmids ( 28 , 70 ), and usually, mer genes are components of transposons ( 71 ), and integrons ( 72 , 73 ). Thus, different copies of the mer genes including maybe different sequence variants ( 29 , 74 ), could be found within a same strain providing to the strains different tolerances to mercury compounds. This specificity is further supported by the fact that no correlation was observed between the ability to reduce Hg and the taxonomic groups observed in the phylogenetic trees, although negative results should be interpreted with caution.…”
Section: Resultsmentioning
confidence: 99%